Culture Analysis in Mohja Kahf’s the Girl in the Tangerine Scarf - Nurfadhlina Sulaiman; Sofyan A. Gani; Kismullah A. Thalib (English Education Journal, 2019)
This research investigates the elements of culture implied in The Girl in the Tangerine Scarf, a novel by Mohja Kahf. This research focused on three aspects: the five cultural elements found in the novel, the Kahf’s description of social and religious common facts, and her description of problems faced by Khadra, the main character as a result of cultural differences. A qualitative method was used to analyze the novel. The data of this research was mainly the novel’s content, Kahf’s narration in the novel. To collect the data, documentation in form of quotation was used. The data were analyzed by using data reduction, data display, and data verification. The result of this research shows that five elements of culture are prominently used in the novel: symbol, language, norm, ritual, and value. Social and religious fact also became the important aspects of this novel. It is also found that attachment of the main characters who are Syrian immigrants to Islamic value became the author’s emphasis throughout the novel. Kahf’s juxtaposition of these Islamic values and the Protestant values held in the part of America where Khadra’s family resided seems to be source of the conflict in the novel. Another elements portrayed in the novel is the contrast between the Syrian’s appreciation of communality and the American’s appreciation of individualism. Lastly, the researcher found that Khadra faced obstacles living in American society.  She is insulted, bullied, attacked, and one of Khadra’s friends was killed by American extremists. It means the culture is very influential in social life especially to adapt in a new environment.